2010
DOI: 10.1038/ajg.2009.558
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Permeability in Cirrhotic Patients With and Without Spontaneous Bacterial Peritonitis: Is the Ring Closed?

Abstract: IP derangement was a common finding in LC, especially in patients with more advanced disease (presence of ascites and history of SBP). The presence of (51)Cr-EDTA in ascites in patients with SBP suggests an altered permeability of splancnic vessels and/or peritoneal membranes. Further studies are required to assess (51)Cr-EDTA urine and ascite cutoffs to set up SBP preventive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 26 publications
4
97
0
5
Order By: Relevance
“…34,35 In a study including 80 cirrhotic patients and 24 controls assessed for intestinal permeability, the risk of SPB and BSI were directly related to the grade of intestinal barrier dysfunction measured by the expression of tight junction protein Claudin-2. 36 …”
Section: Pathophysiology Of Bsis In Patients With Liver Cirrhosis: Inmentioning
confidence: 99%
“…34,35 In a study including 80 cirrhotic patients and 24 controls assessed for intestinal permeability, the risk of SPB and BSI were directly related to the grade of intestinal barrier dysfunction measured by the expression of tight junction protein Claudin-2. 36 …”
Section: Pathophysiology Of Bsis In Patients With Liver Cirrhosis: Inmentioning
confidence: 99%
“…It has been suggested that acid-suppressive therapy with proton pump inhibitors (PPIs), which is widely used in patients with cirrhosis, may increase the risk of bacterial infections, since they cause bacterial overgrowth in the small intestine and increase intestinal permeability [87][88][89][90][91][92] . Several studies, including a meta-analysis [93] of four studies involving a total of 772 patients [94][95][96][97][98] , found significant association between PPI and the development of SBP in patients with cirrhosis (odds ratio 2.77, 95%CI: 1.82-4.23).…”
Section: Secondary Prophylaxis In Patients With Prior Sbpmentioning
confidence: 99%
“…This disturbance allows for overgrowth and translocation of enteric bacteria, typically Gram-negative enteric bacteria (16)(17)(18). Cirrhosis also predisposes an individual to overgrowth of bacterial flora and may lead to increased intestinal permeability (19,20). Deficiencies of local immune response in patients with liver cirrhosis may also contribute to the development of SBP.…”
Section: Discussionmentioning
confidence: 99%